من ذكر أنه لم يرو عنه إلا راو واحد وثبت خلاف ذلك من رجال الكتب الستة - يوسف، يوسف جوده يسن (جامعة الوصل, 2019)
This research seeks to shed light on one of the most important issues of unknown narrators comparing them with the narrators of the six books of Hadith who considered their narrations so weak, not precise and, hence, not authentic. Hadith scholars paid a great interest in studying this sort of narration and wrote many useful specialized books on it. However, the question that arises today is how and when an ‘unknown’ narrator becomes familiar. This issue is discussed in the first descriptive and analytical part of the research. In the second practical part of the research, the biographies of those ‘unknown’ narrators are discussed to determine whether any of the scholars of Hadith proved that other narrators collected Hadith from those unknown ones by weighing the different opinions of scholars, and verifying the different proofs of narrations in all six Hadith Books. The research concludes a statistic of the narrators who have been proved that they have other narrators, and the unknown narrators become familiar which is considered a milestone in accepting or rejecting the narrations.
يدرس هذا البحث مسألة من أدق مسائل علم الرجال، وهي من قال فيهم النقاد: "إنه لم يرو عنه إلا راو واحدا"، أي أنهم وصفوا بجهالة العين فلا يحتج بمروياتهم، ولقد اهتم علماء الحديث قديماً بدراسة هذا النوع، وأفردوا له تصانيف مفيدة، والسؤال الذي يطرح نفسه بقوة، كيف ومتى ترتفع جهالة العين عن الراوي الذي وصف بذلك على الراجح؟، فكان الجواب في الجانب الوصفي التحليلي في المسألة، ثم تناول البحث الجانب التطبيقي لهذه المسألة، فقام الباحث بدراسة وسبر الرواة الذين ذكر النقاد أنهم لم يرو وعنهم إلا راو في الكتب الستة، ثم النظر هل ثبت من كلام أهل الحديث أن لهم رواة آخرين أم لا؟، والترجيح بين أقوال أهل العلم، وإثبات وتحقيق ما ترجح بالأدلة والمرويات عنهم في كتب السنة النبوية، واستخرجت الدراسة نتائج علمية جديرة بالاهتمام، ومن أهمها إحصائية عدد الرواة الذين ثبت أن لهم رواة آخرين، وارتفعت بذلك عنهم جهالة العين، مما يعد علامة فارقة في قبول أو رد المرويات.
Keywords: السنة النبوية -- رواية الأحاديث -- الجرح والتعديل -- الكتب الستة